Effect of antithrombotic therapies on small bowel bleeding: an European multicenter retrospective study - Lucia Scaramella; Stefania Chetcuti Zammit; Reena Sidhu; Maurizio Vecchi; Gian Eugenio Tontini; Nicoletta Nandi; Matilde Topa; Luca Elli (Clinical Endoscopy)
Background/Aims Small bowel bleeding (SBB) is the main indication for videocapsule endoscopy (VCE); the diagnostic yield (DY) could be influenced by antithrombotic therapies. We explored the effects of these therapies on SBB. Methods Consecutive patients from two centers (Milan, Italy and Sheffield, UK) who underwent VCE between March 2001 and July 2020 were considered. Demographic data, clinical parameters, drug therapy, and technical characteristics of the procedure were collected. VCE findings and DY were evaluated. Results In total, 957 patients (1,052 VCEs) underwent VCE for SBB (DY 50.6%, no retention); 27 patients (27 VCEs) received direct oral anticoagulants, 87 (88 VCEs) received other anticoagulants, 115 (135 VCEs) received antiplatelet therapy, 198 (218 VCEs) received monotherapy, and 31 (32 VCEs) received combined therapy. There were no differences in the completion rate, findings, and DYs between each subgroup or between monotherapy and combined therapy. The overt bleeding rate was similar in all groups, even when comparing antithrombotic users versus those not on therapy (p=0.59) or monotherapy versus combined therapy (p=0.34). Conclusions VCE is safe and has a high clinical impact on SBB. Antithrombotic therapies did not affect DY or overt bleeding rate and, consequently, can be considered safe in terms of SBB risk.